TRANSFORMATION OF FINANCIAL REGULATORY GOVERNANCE THROUGH INNOVATION FACILITATORS - CASE STUDY OF INNOVATION HUB IN CROATIAN CAPITAL MARKETS (EU and comparative law issues and challenges series (ECLIC), 2020)
FinTechs have attracted great attention for their potentially disruptive impact on financial ecosystem. They represent a great opportunity for democratisation of financial systems and better access to finance, but also a possible risk for financial stability. Regulatory framework is trailing behind fast-moving technological advancements. Innovation facilitators, i.e. innovation hubs and regulatory sandboxes have been designed as new governance models to promote technological innovations and regulatory efficiency in financial services. The UK is a global pioneer in this area with Project Innovation that started in 2014, while other Member States followed. Croatia has established its first innovation facilitator in a form of Innovation hub in May 2019. The purpose of this paper is to examine the level of financial regulatory innovation and potential for transformation of regulatory governance from “command and control” system to more alternative and collaborative approach characteristic for innovation facilitators. Research methodology combines secondary data, semi-structured interviews and comparative assessment of UK’s and Croatia’s approach to financial regulatory governance, using the most different case method. Results point to incremental changes in governance culture, nonetheless a positive step forward in promoting a culture of dialogue and better policy-making.